2015
DOI: 10.5897/err2015.2434
|View full text |Cite
|
Sign up to set email alerts
|

A study on components of internal control - based administrative system in secondary schools

Abstract: The aim of this study was to study the components of the internal control-based administrative system in secondary schools, and make a Confirmatory Factor Analysis (CFA) to confirm the goodness of fit of empirical data and component model that resulted from the CFA. The study consisted of three steps: 1) studying of principles, ideas, and theories in related documents, 2) synthesizing and specifying them as components of the system, and 3) proposing these components to experts in the field for their confirmati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Lunenburg and Omstein (1996), Katz and Kahn (1978), Bureepakdee (2005), Tedsabutra (2011), Srisaenpang (2013), Patthanajureepan (2013) and Montree (2015). The study result was concluded that the system consisted of four main elements i.e.…”
Section: Methodsmentioning
confidence: 81%
“…Lunenburg and Omstein (1996), Katz and Kahn (1978), Bureepakdee (2005), Tedsabutra (2011), Srisaenpang (2013), Patthanajureepan (2013) and Montree (2015). The study result was concluded that the system consisted of four main elements i.e.…”
Section: Methodsmentioning
confidence: 81%
“…The Control (Operating) environment, Risk assessment, Control activities, Information and Communication, Monitoring [8], [9], [16].…”
Section: Components Of Internal Controlmentioning
confidence: 99%